Randomized Comparison of Terumo® Coated Slender™ versus Terumo® Noncoated Traditional Sheath during Radial Angiography or Percutaneous Coronary Intervention - Birthe Sindberg; Christel Gry Aagren Nielsen; Marianne Hestbjerg Poulsen; Martin Bøhme Rasmussen; Steen Carstensen; Troels Thim; Lars Jakobsen; Jacob Thorsted Sørensen; Benedicte Haastrup; Hanne Maare Søndergaard; Michael Mæng; Christian Juhl Terkelsen (Journal of Interventional Cardiology)
Background. The transradial approach is generally associated with few complications. However, periprocedural pain is still a common issue, potentially related to sheath insertion and/or arterial spasm, and may result in conversion to femoral access. Radial artery occlusion (RAO) following the procedure is also a potential risk. We evaluate whether the design of the sheath has any impact on these variables. Methods. A total of 1,000 patients scheduled for radial CAG or PCI were randomized (1:1) to the use of a Slender or a Standard sheath during the procedure. Randomization was stratified according to chosen sheath size (5, 6, 7 French) and gender. A radial band was used to obtain hemostasis after the procedure, employing a rapid deflation technique. A reverse Barbeau test was performed to evaluate radial artery patency after removal of the radial band, and level of pain was assessed using a numeric rating scale (NRS). Results. Use of the Slender sheath was associated with less pain during sheath insertion (median NRS 1 versus 2, p=0.02), whereas no difference was observed in pain during the procedure, radial procedural success rates, use of analgesics and sedatives during the procedure, and radial artery patency following the procedure. Rate of RAO was 1.5% with no difference between groups. Conclusion. The use of the hydrophilic coated Slender sheath during radial CAG or PCI was associated with less pain during sheath insertion, whereas no difference in other endpoints was observed. A rapid deflation technique was associated with RAO of only 1.5%.